Gac aril and gum xanthan supplementation in wheat macaroni pasta production - Nguyễn Minh Thủy; Nguyen Thi Tieu Phung; Tran Ngoc Giau; Vo Quoc Tien; Ngô Văn Tài; Võ Quang Minh (Acta Scientiarum Polonorum Technologia Alimentaria, 2023)
1Institute of Food and Biotechnology, Can Tho University, Vietnam 2School of Food Industry, King Mongkut’s Institute of Technology Ladkrabang, Thailand 3College of Environment and Natural Resources, Can Tho University, Vietnam
Keywords: Agronomic Practices and Intercropping Systems; Nuts composition and effects; Agriculture and Rural Development Research